Factors associated with older adults’ neglect among relatives in urban areas of Indonesia: a cross-sectional study - Ezalina, Ezalina; Alfianur , Alfianur (Universitas Airlangga, 2025)
Introduction: The aging adult population increases its vulnerability to neglect and other associated risks due to decreased physical and mental competence. Older adults who cannot adapt owing to reduced physical and mental capabilities become dependent on others, particularly family members. Older adults can become neglected if they are not adequately cared for. This study aimed to identify factors associated with neglect among older adults who live with their relatives in Pekanbaru City, Indonesia. Methods: A cross-sectional study with a sample size of 382 Older adults was conducted utilizing multi-stage cluster sampling. The questionnaire measuring tool was conducted through structured direct interviews with the Older adults, specifically to inquire about the variables of Older adults’ neglect, family support, social engagement, and family health tasks, which have been tested for validity and reliability. The data was analyzed using descriptive statistics, the chi-squared test, and binary logistic regression. Results: The neglect experienced by the older adults was high, namely 190 people (49.74%), low, 192 people (50.26%), Family support (p<0.05), family health duties (p<0.05), and social engagement (p<0.05) were associated with Older adults neglect. The binary logistic regression analysis revealed a significant relationship between Older adults’ marital status(widow or widower) and the occurrence of neglect (p<0.05; OR: 29.0; CI: 3.2-25.9). Conclusions: the older adults’ status (married, widow, or widower) significantly influences negligence among older adults.